THE EFFECT OF PLYOMETRIC TRAINING ON SPRINT PERFORMANCE AND EXPLOSIVE STRENGTH IN TRACK AND FIELD ATHLETES - Mugadlimath, Dayanand B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Plyometric training is a widely used method for enhancing sprint performance and explosive strength in track and field athletes. This study investigates the effects of an eight-week plyometric training program on sprint times and lower-body power in competitive sprinters. A total of 40 male and female track and field athletes, aged 18-25 years, were randomly assigned to a plyometric training group (PTG) and a control group (CG). Pre- and post-tests measured 30m and 100m sprint times, vertical jump height, and standing broad jump distance. Statistical analysis revealed significant improvements in the PTG compared to the CG, with reductions in sprint times and increases in jump performance (p < 0.05). These findings suggest that integrating plyometric exercises into training regimens can enhance neuromuscular efficiency, leading to improved sprint speed and explosive strength. This research provides valuable insights for coaches and athletes seeking to optimize performance through scientifically validated training protocols.